STUDI DESKRIPTIF KECEMASAN PADA MAHASISWA AKHIR DALAM MENGERJAKAN TUGAS AKHIR - Novianti, Irene; Chrisellyn, Geraldine; Betari, Indiani Diah (Bali International University, 2022)
Background: final semester students in working on their thesis will certainly find various obstacles in the process. This can cause anxiety in the student. Factors that cause anxiety are internal factors and external factors. Objective: This study aims to determine the description of anxiety in final semester students. Methods: This research uses qualitative research with interview and observation methods to support the research process. Results: The results of interviews with three research subjects showed that the overall research subjects experienced anxiety in working on the thesis, with different durations and different symptoms. Some of the symptoms experienced by all subjects include; shaking, difficulty eating, difficulty sleeping and concentrating, shortness of breath, cold sweats and abdominal discomfort. Conclusion: Moderate anxiety experienced by students who are preparing their thesis is characterized by several common manifestations during the thesis preparation process such as easy to cry when finding difficulties during the thesis preparation process, easily forgetting the explanation of the supervisor after consulting, easily offended when finished consulting and feeling uncomfortable. can't wait to go to trial